Peningkatan Pengetahuan Imunisasi Tetanus Toxoid Sebagai Upaya Promotif untuk Cegah Infeksi Tetanus - Richa, Fadhila Tsania (Journal of Midwifery in Community, 2023)
The Tetanus Toxoid immunization program to prepare for pregnancy before marriage has not yet achieved the expected results. The low coverage of Tetanus Toxoid is that people's knowledge is still low and attitudes are not yet supportive of carrying out Tetanus Toxoid immunization practices. The purpose of this activity is to increase public knowledge,especially women of childbearing age, about the importance of Tetanus Toxoid immunization before marriage or before pregnancy. The method used in this service is the lecture method by providing counseling to the public about the importance of Tetanus Toxoid immunization for mothers and babies. The materials used are in the form of posters, power points, and zoom meetings which are distributed to the public in the form of soft files. The result of this service is an increase in public knowledge, especially women of childbearing age, about the importance of Tetanus Toxoid immunization for themselves and their babies. People also increasingly understand the importance of Tetanus Toxoid immunization before marriage. Counseling went well, the community understood how important it was to prepare Tetanus Toxoid immunization before marriage for the health of mothers and their babies.